Case report: Surgical treatment of an astrocytoma in the thoracic spinal cord of a cat - Santifort, Koen M.; Tamura, Shinji; Rissi, Daniel R.; Grinwis, Guy C. M. (Frontiers in Veterinary Science, 2023)
A 15-year-old spayed female domestic shorthaired cat was evaluated for chronic progressive paraparesis and proprioceptive ataxia. Neurological examination was consistent with a T3-L3 myelopathy. Plain thoracolumbar vertebral column radiographs and CT without intravenous contrast or myelography performed at another facility did not highlight any abnormalities. MRI of the thoracolumbar spinal cord identified an intraparenchymal space-occupying lesion extending from T10-T12. Surgery was performed to remove as much of the mass as possible, and to submit samples for histopathology. A dorsal laminectomy was performed over T9-T13. A midline myelotomy provided access to the mass, which was debrided with an intraoperative estimate of 80% removal. Histopathologic examination was consistent with a diagnosis of an astrocytoma. Post-operative treatment consisted of amoxicillin clavulanic acid, prednisolone, gabapentin, and additional analgesic medications in the direct post-operative period. Over the following 4 months, slow recovery of motor function was seen with continued physiotherapy. During the following 2 months, renal and cardiopulmonary disease were diagnosed and treated by other veterinarians. The cat was also reported to have lost voluntary movement in the pelvic limbs during this period, suggesting regression to paraplegia. Finally, 6 months post-surgery, the owner elected humane euthanasia. This is the second documentation of surgical treatment and outcome of an astrocytoma in the spinal cord of a cat.